A budget optimisation model for road safety infrastructure countermeasures. Issue 1 (31st December 2022) - Byaruhanga, Chris Bic; Evdorides, Harry
Abstract: The requirements and modifications to the road infrastructure to achieve high levels of safety require different countermeasures that are not directly comparable considering their life span. It is felt that the effectiveness of a road safety programme highly depends on the best mix between capital and maintenance work measures. To this end, this article introduces a novel methodology that prioritises countermeasures by considering their effectiveness over their life span together with budget constraints, based on a mixed integer linear programming model with an objective function to maximise their economic safety benefits. To illustrate the application of the proposed model developed using the LINGO software, a case study from the Netherlands, Utrecht provincial roads, was used. The results show that this approach seems to enhance both the prioritisation and the number of countermeasures selected for implementation. Furthermore, the method can compute the minimum budget required to maximise the economic benefits from capital work measures. It may also prioritise road safety-related maintenance work programmes and offer a plan for capital works if funds are below the minimum budget. Consequently, this approach appears to enhance the non-life span approach due to an improved mix between capital and maintenance work programmes for road safety.